Flashcards Application As A Learning Media To Improve The Ability To Recognize Colors In English For Early Childhood Education Children And Kindergarten Children - Minalti; Cucut Annaningtyas; Sri wahyuni Samaratul Zanah (MULTIPLE: Journal of Global and Multidisciplinary, 2024)
This study aims to examine the effectiveness of using flashcards in improving color recognition skills in kindergarten children. The method used is an experiment with a pretest-posttest design. The research sample consists of 30 kindergarten children who were divided into two groups: an experimental group (class B) that used flashcards and a control group (class A) that used conventional methods. The results showed that children in the experimental group experienced a significant improvement in their ability to recognize colors compared to the control group. These findings indicate that flashcards are effective as a learning medium for introducing colors to kindergarten children.